Yeast-fermented Curcuma longa as a natural alternative to antibiotics for enhancing broiler chicken performance - Malahubban, Masnindah; Ab Aziz, Zakry Fitri; Mohd Ali Hanafiah, Muhamad Hakim; Mustafa, Suhaili; Kamaludeen, Juriah (2024)
This study evaluated the effects of dietary supplementation with yeast-fermented Curcuma longa on growth performance and mortality in broiler chickens, comparing it with conventional antibiotic treatment. A total of 160 Ross 308 broilers were divided into four groups: T1 (control), T2 (tetracycline antibiotics), T3 (1% yeast-fermented Curcuma longa), and T4 (2% yeast-fermented Curcuma longa). From day 21 to 35, growth rates were lowest in the control group (T1), while the T4 group showed the highest growth rate (1783.58 g) by day 35. Feed Conversion Ratio (FCR) analysis indicated that 2% yeast-fermented Curcuma longa provided superior feed efficiency, particularly from days 28 to 35, outperforming both the control and antibiotic groups. Notably, both 1% and 2% yeast-fermented Curcuma longa eliminated mortality, unlike the control and antibiotic-treated groups, which had higher mortality rates. These results suggest that yeast-fermented Curcuma longa, especially at 2%, significantly improves growth and feed efficiency in broiler chickens, offering a promising natural alternative to antibiotics. This could help reduce antibiotic use, mitigate antimicrobial resistance, and support sustainable poultry farming practices.